Harry Houdini : Photographic Story of a Life. - Cobb, Vicki (New York, NY : DK Publishing Company, 2005)
A photographic story of the fascinating life of Harry Houdini.
Keywords: Houdini, Harry - Biography - Juvenile literature; Magicians - United States - Biography - Juvenile literature; Escape Artists - United States - Juvenile literature; Harry Houdini, A Photographic Story of a Life